Ultrafast Investigation of Individual Bright Exciton–Plasmon Polaritons in Size‐Tunable Metal–WS2 Hybrid Nanostructures. Issue 10 (5th March 2020) - Chowdhury, Rup K.; Datta, Prasanta K.; Bhaktha, Shivakiran N. B.; Ray, Samit K.
Abstract: Strong light–matter interactions between resonantly coupled metal plasmons and spin–orbit‐coupled bright excitons from 2D transition metal dichalcogenides (TMDs) can produce discrete bright exciton–plasmon polaritons (plexcitons). A few efforts have been made to perceive the spin‐induced exciton‐polaritons in nanocavities at cryogenic conditions, however, successful realization of bright plexcitons in time domain is still lacking. Here, both the bright plexcitons are identified discretely at room temperature and their ultrafast temporal dynamics in size‐tunable Au–WS2 hybrid nanostructures are investigated using a helicity‐controlled femtosecond pump‐probe spectroscopy technique. The zero detuning between both the bright excitons and plasmons is achieved at ≈7.0 ps, matching with the stable plexciton formation time. The Rabi‐splitting energy is as high as ≈250 meV for both the plexcitons, validating the strong‐coupling conditions of polariton formation. Realization of these novel bright exciton–plasmon interactions in the metal–TMDs platform is, therefore, interesting for both fundamental understanding and their possible futuristic applications in quantum photonics operating at room temperature. Abstract : Ultrafast real‐time observation of individual bright exciton–plasmon polaritons in Au nanostructures–layered WS2 hybrids is reported through helicity‐controlled pump‐probe spectroscopy technique at room temperature. Introducing metal nanostructures with specific dimensions, discrete anticrossing is attributed to strong coupling of individual bright excitons and plasmons in time domain. Both the polaritons show high Rabi‐splitting energies with similar stable plexciton formation times.